Space Weather in the Popular Media, and the Opportunities the Upcoming Solar Maximum Brings - Brett A. Carter; Noé Lugaz; Steven K. Morley; Jennifer Gannon; Shasha Zou; Huixin Liu (Space Weather)
Abstract The media interest/coverage of space weather has been increasing as we approach solar maximum and the private space industry has grown significantly since the last significant solar maximum in 2000–2002. It is not uncommon for space weather media coverage to use hyperbole with frequent references to the infamous “Carrington event.” The implications of associating each of the many upcoming moderate‐to‐severe storms with the Carrington event are discussed, and we encourage the curbing of hyperbole whenever possible. While there is an excellent but small cohort of space weather researchers actively engaging with the media, we urge more (particularly early‐to‐mid career) to take advantage of media training resources and to join in. We also call for these efforts to be broadly supported by peers and institutions for the benefit of space weather as a discipline.